2011
DOI: 10.1089/omi.2010.0141
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquity of the Insulin Superfamily Across the Eukaryotes Detected Using a Bioinformatics Approach

Abstract: The insulin superfamily is composed of a diverse group of proteins that share a common structural design whose most notable feature is a set of disulfide bonds. There is now sufficient experimental and bioinformatics evidence that it is represented in at least a number of well-investigated invertebrates, where they have been found to intervene mainly in complex processes such as mitosis, cell growth, castes differentiation, and fertility. In this article we automated a methodology first proposed elsewhere-that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Insulin and related peptides (insulin-like peptides, insulin-like growth factors and relaxins) form a large superfamily of peptide hormones (Shabanpoor et al, 2009) that is found throughout the animal kingdom (Piñero-González and González-Pérez, 2011). In vertebrates, insulin is synthesized in pancreatic β-cells and is the key regulator of carbohydrate and fat metabolism (Blumenthal, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and related peptides (insulin-like peptides, insulin-like growth factors and relaxins) form a large superfamily of peptide hormones (Shabanpoor et al, 2009) that is found throughout the animal kingdom (Piñero-González and González-Pérez, 2011). In vertebrates, insulin is synthesized in pancreatic β-cells and is the key regulator of carbohydrate and fat metabolism (Blumenthal, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3−5 In Homo sapiens, the insulin superfamily consists of ten members: insulin, insulin-like growth factors (IGF) I and II, and a relaxin subfamily that comprises relaxin-1, -2, and -3 and four other insulin-like peptides (INSL 3, 4, 5, and 6). 3,5,6 IGFs I and II are unique in that they both possess a single peptide chain structure that is cross-linked by three disulfide bonds in the same disposition as for insulin. Whereas insulin and IGFs I and II interact with tyrosine kinase receptors, the members of the relaxin subfamily interact with G-protein-coupled receptors known as relaxin family peptide receptors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The insulin superfamily is a large, ubiquitous group of peptides with diverse physiological activities found throughout the animal kingdom . A recent analysis using a sequence similarity algorithm identified insulin‐like peptides in 46 vertebrate and invertebrate genomes . The family name derives from its oldest and most prominent member, insulin, a hormone of immense historical and medicinal importance.…”
Section: Introductionmentioning
confidence: 99%